bicoid RNA localization requires specific binding of an endosomal sorting complex - Irion, Uwe (2007)
bicoid mRNA localises to the anterior of the Drosophila egg, where it is translated to form a morphogen gradient of Bicoid protein that patterns the head and thorax of the embryo. Although bicoid was the first identified localised cytoplasmic determinant1-4, little is known about how the mRNA is coupled to the microtubule-dependent transport pathway that targets it to the anterior, and it has been proposed that it is recognised by a complex of many redundant proteins, each of which binds to the localisation element in its 3'UTR with little or no specificity5. Indeed, the only known RNA-binding protein that co-localises with bicoid mRNA is Staufen, which binds non-specifically to dsRNA in vitro6, 7. Here we show that mutants in all subunits of the ESCRT-II complex (Vps22, Vps25 and Vps36) abolish the final Staufen-dependent step in bcd RNA localisation. ESCRT-II is a highly conserved component of the pathway that sorts ubiquitinated endosomal proteins into internal vesicles8, 9, and functions as a tumour-suppressor by removing activated receptors from the cytoplasm10, 11. However, the role of ESCRT-II in bicoid localisation appears to be independent of endosomal sorting, because mutations in ESCRT-I and III components have no effect of the targeting of bicoid mRNA. Instead, Vps36 functions by binding directly and specifically to stem-loop V of the bicoid 3'UTR through its N-terminal GLUE domain12, making it the first example of a sequence specific RNA-binding protein that recognises the bicoid localisation signal. Furthermore, Vps36 localises to the anterior of the oocyte in a bicoid mRNA-dependent manner, and is required for the subsequent recruitment of Staufen to the bicoid complex. This novel function of ESCRT-II as an RNA-binding complex is conserved in vertebrates, and may explain some of its roles that are independent of endosomal sorting.